PENERAPAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN AKTIVITAS SISWA DALAM PEMBELAJARAN IPA SISWA KELAS IIIB SD NEGERI 191 PEKANBARU - Sagita Desriani; Mahmud Alpusari; Zariul Antosa (Jurusan Ilmu Pendidikan, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Riau, 2019)
The problem in this study is the lack of student activity because of the lack of conformity to the learning model with the science learning process, causing a lack of student activity in science learning. This research is to increase the activity of class IIIB students in Pekanbaru. Elementary School in science learning by applying the Contextual Teaching and Learning (CTL) model. This study uses classroom action research. The data in this study are quantitative. This can be seen from the percentage of student activity in the initial visual observations on student activities paying attention to the teacher with a 42.8% increase. In the activity of observing the experiment with an increase of 86.1%. In oral activities on the activity of issuing opinions with a 66.6% increase. In students, activities ask with an increase of 19.4%. On listening activities, when listening to teachers with an increase of 42.88%. On the activity of hearing the results of group discussions with an increase of 80.5%. In writing activities, the activity of writing experimental results with an increase of 50%. In the activity of evaluating with an increase of 49.91%. Drawing activity with 41.6% increase. In the metric activity, the activity of choosing tools and materials with a 75% increase. The activity carried out experiments with an increase of 72.2%. From the explanation above that by applying the Contextual Teaching and learning model can increase the activity of students in science learning students of class IIIB SD Negeri 191 Pekanbaru.